Interchange student's book 1a - Richards, Jack C; Hull, Jonathan (New York: Cambrige University Press, 2005)
Los temas principales son: Plan of book 1, The new editon, Student?s Book overview, Teaching notes, Please call me beth, How do you spend your day, How much is it, Do you like rap, Tell me about your family, How often do you exercise
1 CD de audio
Keywords: Lenguaje - Inglés